Items from Germany-The impact of Rht alleles on cross-pollination efficiency traits with relevance for hybrid breeding in wheat - Schierenbeck, Matías (2022)
Hybrid breeding and the ability to exploit heterosis is one of a few high-priority wheat breeding strategies that have the potential to rapidly improve yield and stability. Yield improvements associated with hybrid vigor were demonstrated to be in the order of a 10–25% increase in grain yield as well as improved resistance against biotic/abiotic stresses and grain quality. Faced with these scenarios, the identification of factors affecting the development of hybrid wheats is of fundamental importance in order to accelerate the rate of genetic gain of the crop. Due to the prevalence and usefulness of Rht ‘Green revolution’ dwarfing alleles, it is important to gain a better understanding of how these alleles affect those traits related to the development of hybrid wheat seed production. Up to now, the expected influence of these alleles/ genes on wheat flowering-related traits was evaluated based on mapping populations or genome-wide association studies, without taking into account the actual effect of each Rht allele in particular. In this project, we propose to explore the effect of different Rht alleles using many near-isogenic lines. The experiments were performed at the Leibniz Institute of Plant Genetics and Crop Plant Research (IPK Gatersleben, Germany) and the Faculty of Agricultural Sciences and Forestry (National University of La Plata, Argentina) during three growing seasons. Four sets of NILs carrying the alleles of Rht genes: Rht1 (Rht-B1b/Rht-D1a), Rht2 (Rht-B1a/Rht-D1b), Rht3 (Rht-B1c/Rht-D1a), Rht 1+2 (Rht-B1b/ Rht-D1b), Rht 2+3 (Rht-B1c/Rht-D1b), and rht (tall; Rht-B1a/Rht-D1a) in the genetic backgrounds of the wheat cultivars April Bearded, Bersee, Maris Huntsman, and Maris Widgeon were evaluated. Traits associated with cross-pollination efficiency (flowering date, plant height, spike length, anther extrusion, anther and filament length, and spikelets/spike) were studied. Preliminary results showed that the extreme dwarf alleles Rht3, Rht1+2, and Rht2+3 presented the greatest effects in all the variables analyzed. Plant height showed reductions from 22–25% (Rht1 and Rht2), 50–57% (Rht3 and Rht1+2), and 66% (Rht2+3) compared to rht (tall). Spike length was increased up to 14% (Rht1+2 vs. rht) and 3–9% for the rest of Rht alleles compared to rht, whereas spikelets/spike were increased up to 6% (Rht2+3 vs. rht). In comparison to rht (tall), the floral organs were negatively influenced by Rht alleles; decreases from 8–13% (Rht 1, Rht2, and Rht3) to 17–25% (Rht1+2 and Rht2+3) in anther length, and reductions from 16–44% in filament length were observed. For their part, anthers extrusion decreased between 15–27% (Rht1, Rht2, and Rht3) to 32–35% for Rht1+2 and Rht2+3 compared with that of rht. No significant differences were detected for flowering time among the alleles evaluated. These preliminary results indicate that Rht alleles combination are involved in multiple traits of interest for hybrid wheat production in breeding programs. Moreover, the magnitude of the negative impact of Rht alleles on floral organs depends on the combination of the alleles involved.